Functional genomic analysis of corals from natural CO2‐seeps reveals core molecular responses involved in acclimatization to ocean acidification. (5th September 2017) - Kenkel, Carly D.; Moya, Aurelie; Strahl, Julia; Humphrey, Craig; Bay, Line K.
Abstract: Little is known about the potential for acclimatization or adaptation of corals to ocean acidification and even less about the molecular mechanisms underpinning these processes. Here, we examine global gene expression patterns in corals and their intracellular algal symbionts from two replicate population pairs in Papua New Guinea that have undergone long‐term acclimatization to natural variation in pCO2 . In the coral host, only 61 genes were differentially expressed in response to pCO2 environment, but the pattern of change was highly consistent between replicate populations, likely reflecting the core expression homeostasis response to ocean acidification. Functional annotations highlight lipid metabolism and a change in the stress response capacity of corals as key parts of this process. Specifically, constitutive downregulation of molecular chaperones was observed, which may impact response to combined climate change‐related stressors. Elevated CO2 has been hypothesized to benefit photosynthetic organisms but expression changes of in hospite Symbiodinium in response to acidification were greater and less consistent among reef populations. This population‐specific response suggests hosts may need to adapt not only to an acidified environment, but also to changes in their Symbiodinium populations that may not be consistent among environments, adding another challenging dimension to the physiological process of coping with climate change. Abstract : Acropora millepora corals from replicate volcanic CO2 seep sites exhibit small but consistent gene expression changes, including alteration of lipid metabolism and heat shock proteins, that likely reflects their core homeostasis response to ocean acidification. Responses of in hospite Symbiodinium were greater but less consistent among reef sites, suggesting that corals may need to adapt not only to acidification, but to changes in their symbionts, adding another challenging dimension to the physiological process of coping with climate change.